PERAN WAKAF UANG DALAM MENDUKUNG PROGRAM FASILITAS PENGELOLAAN SAMPAH ANTARA (STUDI KASUS PADA BADAN WAKAF INDONESIA) - Bhekti Jatining Putri; M. Umar Burhan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
The Special Capital Region of Jakarta is one of the twelve provinces that receive the mandate for establishing a waste-powered electric generator (the Intermediate Treatment Facility), which is popular with the name of FPSA, an Indonesian acronym for Intermediary Waste Management Facility. However, since its inauguration in 2018, the development has not taken place until 2022 due to fund shortage. The cause is the high construction cost, in which the budget of IDR 3 trillion is too much for the local budget to cover, making the project stopped. Until 2021, the amount of cash waqf in Indonesia has reached IDR 180 trillion. That sum of money is potential to be used as a funding alternative for the project. This descriptive qualitative research discusses how cash waqf paly its role in supporting the FPSA program using case study approach. The primary data examined here were obtained from interviews. The results show that the potential and the reality of cash waqf can support the FPSA program through small aid scale and that the use of waqf-through-money scheme is more suitable for the construction of FPSA .